Effect of Essential Oils and Feed Enzymes on Performance and Nutrient Utilization in Broilers Fed a Corn/Soy-based Diet - Cao, P.H.; Li, F.D.; Li, Y.F.; Ru, Y.J.; Peron, A.; Schulze, H.; Bento, H. (International Journal of Poultry Science, 2010)
The objective of this study was to assess the effect of an encapsulated blend of Essential Oils (EOS) and a cocktail of various Enzymes (ES) including phytase and xylanase on the performance and nutrient utilization in broilers fed a corn/soy-based diet reduced in calcium, phosphorus and AME. Total 640 one day-old male chickens were allocated to 4 dietary treatments, following a 2 x 2 factorial design, 2 inclusion levels of EOS (0 or 100 g/t of feed) and 2 inclusion levels of ES (0 or 350 g/t of feed). The results indicated that there was no interaction in performance of broilers between EOS and ES. During the first three weeks, the mortality of broilers fed the diet containing EOS was lower (p